Implementation Of Fun Learning Method In BTQ Learning To Improve Student Learning Outcomes - Dewi Siani, Selfiana; Haryanto, Budi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research examines the implementation of the fun learning method in BTQ learning to improve student learning outcomes. The Qu'an Reading and Writing subject is an important component in the school curriculum, and the quality of teaching can vary depending on various factors, including the school quality category. This research uses quantitative methods and involves ustad applying fun learning methods in learning the Al-Qur'an at MI Islamiyah Cangkringan Sukodono Sidoarjo. The research aims to evaluate and understand the practice of fun learning methods. This research also explores the perceptions of ustad, madrasah ibtidaiyah caregivers, and students regarding fun learning methods. This research uses classroom action (PTK). The research subjects were Qur'an reading and writing (BTQ) teachers at MI Islamiyah Cangkringan Sukodono Sidoarjo. Data collection was carried out through interviews with Qur'an reading and writing teachers, homeroom teachers and students. The data analysis process usually involves several stages, including data reduction, data presentation, and drawing conclusions. The results of this research are that the fun learning method can be recommended as BTQ learning (reading and writing the Qur'an) in improving student learning outcomes. This is shown in the simple t-pride test. The fun learning method can be a method in BTQ learning to improve student learning outcomes based on classroom action research.